2019
DOI: 10.3390/ani9030071
|View full text |Cite
|
Sign up to set email alerts
|

Dietary β-Sitosterol Improves Growth Performance, Meat Quality, Antioxidant Status, and Mitochondrial Biogenesis of Breast Muscle in Broilers

Abstract: The present study evaluated effects of β-sitosterol on growth performance, meat quality, oxidative status, and mitochondrial biogenesis of breast muscle in broilers. One-day-old chicks were allocated to five treatments of six replicates. Broilers were fed a basal diet supplemented either with 0 (control), 40, 60, 80, or 100 mg/kg β-sitosterol for 42 days. β-sitosterol linearly and quadratically reduced feed/gain ratio, lightness24h and cooking loss24h in breast muscle, whereas 2, 2-diphenyl-1-picrylhydrazyl sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 44 publications
3
23
0
Order By: Relevance
“…Manipulation of diets by different treatments can improve the meat quality in poultry ( Cheng et al., 2019 ). The higher pH value at 24 h (pH 24 h ) in the breast muscle of broilers fed CWE-supplemented diets might be a good indicator of meat quality because its declining rate is associated to meat tenderness ( Lonergan et al., 2010 ; Guimarães et al., 2014 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Manipulation of diets by different treatments can improve the meat quality in poultry ( Cheng et al., 2019 ). The higher pH value at 24 h (pH 24 h ) in the breast muscle of broilers fed CWE-supplemented diets might be a good indicator of meat quality because its declining rate is associated to meat tenderness ( Lonergan et al., 2010 ; Guimarães et al., 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Duplicate measurement of sample was performed, and the average values were considered as the final values. Drip loss was measured according to Cheng et al. (2019) .…”
Section: Methodsmentioning
confidence: 99%
“…Manipulating diets by different treatments can improve the meat quality in poultry (Cheng et al 2019). Lower pH and water-holding capacity increases the losses of soluble nutrients that ultimate leads to poor quality of meat (Ozturk et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The determination method of pH was followed by Shang et al (2014). The drip loss of breast muscle and thigh muscle were measured according to Cheng et al (2019). Briefly, the samples were trimmed and weighed, then placed in an inflated plastic bag and hung for 24 h at 4 C. After 24 h, the samples were weighed again.…”
Section: Meat Quality Analysismentioning
confidence: 99%
“…β-sitosterol is the most abundant phytosterol, and it has been shown to reduce the absorption of cholesterol and the serum level of cholesterol in previous studies. It has been reported that BSS has many biological activities, such as cholesterol-lowering [15], anticancer [16], antioxidant [17], and anti-inflammatory [18]. Furthermore, several studies have been demonstrated that BSS ameliorated high-fat diet-induced intestinal inflammation in mice [19], suppressed the secretion of inflammatory factors from keratinocytes and macrophages induced by LPS, such as TNF-α, IL-1β, IL-6, and IL-8, respectively [20].…”
Section: Introductionmentioning
confidence: 99%